Lever of empire : the international gold standard and the crisis of liberalism in prewar Japan - Metzler, Mark, 1957- (Twentieth-century Japan, 2006)
This book, the first full account of Japan's financial history and the Japanese gold standard in the pivotal years before World War II, provides a new perspective on the global political dynamics of the era by placing Japan, rather than Europe, at the center of the story.